Correlation Between Protein Intake and Nitrogen Balance of Surgical Patients in Anesthesiology and Intensive Care Installation, Sanglah General Hospital, Denpasar, Bali, Indonesia - Wiryana, Made; Sinardja, I Ketut; Senapathi, Tjokorda Gde Agung; Widnyana, I Made Gede; Panji, Putu Agus Surya; Aryabiantara, I Wayan; Cindryani, Marilaeta (BALI MEDICAL JOURNAL, 2016)
Background: A cell injury from surgical stress in a trauma or a non-trauma case will induce a hyper  metabolic response in which the protein degradation increases, the somatic protein synthesis decreases  and the amino acid catabolism increases. Thus, the pyper metabolic response contributes to nitrogen  loss in urine. This response, without an adequate nutrition, will lead an iatrogenic malnutrition and  deterioration. A balance nitrogen formula through urinary urea nitrogen is one of many nutrition  evaluation methods. This method aids in evaluating the daily nutrition status and it can be the baseline  data for daily intake. Objective: To find a correlation between the protein intake and the nitrogen  balance of the surgical patients in anesthesiology and intensive care installation, Sanglah General  Hospital, Denpasar, Bali. Methods: Fifty-one surgical patients with trauma and non-trauma cases were  observed for their protein intake for 2-3 days continuously. Moreover, they were evaluated for their  nitrogen balance based on the urinary urea nitrogen per 24 hours for 2-3 days. For statistical analysis,  we utilized Shapiro-Francia, Shapiro-Wilk, Spearman Frank correlation, two-sample t test, and  multivariate regression analysis in Strata SE 12.1. Results: The correlation between the protein intake  and the nitrogen balance on the first day was r a =0.50 (p<0.05), on the second day r a =0.70 (p<0,05), and  on the third day r a =0.740 (p<0,05)  Conclusions: There is a correlation between the protein intake and  the nitrogen balance of surgical patients in Anesthesiology and Intensive Care Installation Sanglah  General Hospital Denpasar.
Keywords: protein intake, nitrogen balance, Urinary Urea Nitrogen, correlation.